THE RELATIONSHIP BETWEEN SELF-CONCEPT AND CAREER CHOICE OF STUDENTS IN CLASS IX JUNIOR HIGH SCHOOL - Huda, Abror Ikhtiyar Zaemur; Ismanto, Heri Saptadi; Kusumawati, Mia Indah (Jurusan Bimbingan dan Konseling, 2024)
The study regarding the correlation between self-concept and career choices of students at Junior High School Semarang IX began with students' confusion in determining their career choices after graduating. Students are expected to know values, interests, skills, intelligence and personality so that students can be creative and find ways to plan their future lives. This encourages students to understand strengths, weaknesses, obstacles and how to overcome problems. The aim of this research is to find out whether there is a correlation between self-concept and career choice? This research applies a quantitative correlational approach with a descriptive research type where the correlation method was chosen because the researcher wanted to see the correlation between students' self-concept and career choices using the cluster random sampling technique, namely a random sampling technique from the population based on the main population classes. Based on the correlation test results, a correlation value of 0.556 > 0.244 was calculated. Thus, it can be concluded that there is a significant correlation between self-concept and the career choices of students at Junior High School Semarang.